Dissociative Identity Disorder Reflected in Frederick Cleggâs Character in `The Collectors` Novel - Asia, Janitra; Samanik, Samanik (English Language and Literature International Conference (ELLiC) Proceedings, 2018)
This paper discusses dissociative identity disorder as seen in John Flowlessâ novel entitled The Collectors. The main purpose of this research is to reveal the causes of dissociative identity disorder and the symptoms of dissociative identity disorder in the novel. The writer focuses of the main character who named Frederick Clegg. The writer arranges the literary review by discussing about theory and approach. The theory that is used dissociative identity disorder by Pierre Janet. Dissociative identity disorder is characterized by the presence in one individual of two or more alternative personality states (alters). For such individuals, the memory representation of a particular event can have full episodic, auto noetic status for one alter, while having the status of knowledge or even being inaccessible to a second alter this analysis applied qualitative and library research to depict clearly about the problem by using the words. The result of this analysis shows some causes and symptoms that exist in the novel. For the causes it was started from capacity for dissociation, traumatic experiences, perpetuating factors. Meanwhile for the symptoms are start from memory loss (amnesia), mental health problems, such as depression, anxiety, and suicidal thoughts and behaviors. The writer hope that by conducting this research it can be use full for the future reader that are interested in the same theory.